2019
DOI: 10.1177/1359105318820690
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the body and appearance self-conscious emotions scale in Brazilian adolescents

Abstract: This study examined the psychometric properties of the Body and Appearance Self-Conscious Emotions Scale in Brazilian adolescents. A sample of 827 adolescents (55% boys) filled out a questionnaire comprising the Body and Appearance Self-Conscious Emotions Scale and instruments assessing social physique anxiety, positive/negative affect, and self-esteem. After removing one item originally proposed for the guilt factor (Item 7), the results supported a 4-factor structure that was invariant across gender and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
(81 reference statements)
4
13
0
Order By: Relevance
“…BASES scores also had adequate internal consistency coefficients and 2-week temporal stability. Broadly speaking, these results are consistent with previous investigations examining the factor structure of the BASES scores in other linguistic and cultural groups (Castonguay et al, 2014, 2017; Chiminazzo et al, 2019; Razmus et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BASES scores also had adequate internal consistency coefficients and 2-week temporal stability. Broadly speaking, these results are consistent with previous investigations examining the factor structure of the BASES scores in other linguistic and cultural groups (Castonguay et al, 2014, 2017; Chiminazzo et al, 2019; Razmus et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The factor structure and psychometric properties of the BASES were also supported in a sample of English-speaking Canadian youth (Castonguay et al, 2017), and certain linguistic and cultural samples outside of Canada including Poland (Razmus et al, 2019; Razmus and Razmus, 2017), Brazil (Chiminazzo et al, 2019; Souza Santos et al, 2017), and Spain (Alcaraz-Ibáñez and Sicilia, 2018). Past research has positively (or negatively) associated body- and appearance-related guilt and shame with several disruptive (or adaptive/healthy) behaviors and cognitions.…”
Section: Introductionmentioning
confidence: 79%
“…Body-related self-conscious emotions regulate individual’s thoughts and feelings and motivate behaviors; that is why they have important well-being and health-related implications. For instance, body shame is associated with depression (Brunet et al, 2019) or negative affect (Chiminazzo et al, 2019), whereas guilt is related to obsessive–compulsiveness and body dysmorphic disorder (Zemestani et al, 2019) and may increase susceptibility to eating disorders (Calogero and Pina, 2011). On the other hand, body-related guilt may serve as a motivator of reparative activities, such as exercising to burn calories after eating too much (Sabiston et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The BASES (Castonguay et al, 2014) has been validated in Polish adults (Razmus et al, 2018), Spanish undergraduates (Alcaraz-Ibáñez and Sicilia, 2018), students in Iran (Zemestani et al., 2019), and Brazilian adolescents (Chiminazzo et al, 2019). All validation studies provided evidence for the expected four-factor structure of the scale, although research in Spain and Brazil indicated ambiguous nature of Item 7 (Guilt) which was removed as a consequence in the both linguistic versions of the scale.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, future work should also seek to include additional measures that would help to evidence the construct validity of BAS-2 scores. This might include measures that have been validated for use in Brazilian adults, including measures of intuitive eating (da Silva et al, 2019) and body and appearance self-conscious emotions (Chiminazzo, Alcaraz-Ibáñez, & Sicilia, 2019).…”
Section: Discussionmentioning
confidence: 99%